Both soap and ozone more effective and better tolerated than alcohol hand disinfection?. (30th September 2020) - Breidablik, H; Johannessen, L; Andersen, J; Lysebo, D; Skare, Å; Kleiven, O T
Abstract: Background: Preventing the transfer of virulent microorganisms is an essential part of infection control programs and clinical practice. Hand disinfection using alcohol from dispensers has become a standard practice worldwide; however, consequent skin irritation is frequently reported. Thus, alternative methods for hand sanitization are needed. Objectives: We used a modified European Standard procedure (EN 1500:2013) with the aim of comparing the efficiency of alcohol, ozonated water and soap for eradicating transient Escherichia coli from artificially contaminated hands. Methods: We applied a crossover design for testing alcohol and ozone (20 participants/product; 40 participants in total). The participants were mostly nursing students. We have merged the results from two separate crossover studies with altogether 35 participants, and also included 20 non-crossover participants for soap washing. Results: Both ozonated tap water and soap & water were more effective than alcohol disinfection; and washing hands with soap the most effective. In some participants, disinfection with alcohol seemed to fail at eradicating transient E. coli from the hands, particularly from one side. The pre-test CFU/mL values were ≥30, 000 in 52 of 55 participants. After disinfection of both the hands with 85% alcohol, 0.8 ppm ozonated tap water and soap & water, the mean/median (range) values were 2330/300 (14, 000), 538/250 (3450) and 98/50 (450), respectively. The majority of the participants (66%) stated that they would prefer using ozonated tap water if the disinfection effect was the same as that of other agents. Conclusions: We hypothesize that hand disinfection with alcohol is more difficult, and that the flow rate of water may play a pivotal role in eradicating microorganisms in addition to the choice of disinfectant. Ozonated tap water had no adverse effects on the skin and was preferred by most participants. Key messages: Ozonized water as hand disinfection. Alcohol hand disinfection problems.